Vascular Aging in the Invertebrate Chordate, Botryllus schlosseri - Rodriguez, Delany; Taketa, Daryl A.; Madhu, Roopa; Kassmer, Susannah; Loerke, Dinah; Valentine, Megan T.; Tomaso, Anthony W. De (Frontiers in Molecular Biosciences, 2021)
Vascular diseases affect over 1 billion people worldwide and are highly prevalent among the elderly, due to a progressive deterioration of the structure of vascular cells. Most of our understanding of these age-related cellular changes comes from in vitro studies on human cell lines. Further studies of the mechanisms underlying vascular aging in vivo are needed to provide insight into the pathobiology of age-associated vascular diseases, but are difficult to carry out on vertebrate model organisms. We are studying the effects of aging on the vasculature of the invertebrate chordate, Botryllus schlosseri. This extracorporeal vascular network of Botryllus is transparent and particularly amenable to imaging and manipulation. Here we use a combination of transcriptomics, immunostaining and live-imaging, as well as in vivo pharmacological treatments and regeneration assays to show that morphological, transcriptional, and functional age-associated changes within vascular cells are key hallmarks of aging in B. schlosseri, and occur independent of genotype. We show that age-associated changes in the cytoskeleton and the extracellular matrix reshape vascular cells into a flattened and elongated form and there are major changes in the structure of the basement membrane over time. The vessels narrow, reducing blood flow, and become less responsive to stimuli inducing vascular regression. The extracorporeal vasculature is highly regenerative following injury, and while age does not affect the regeneration potential, newly regenerated vascular cells maintain the same aged phenotype, suggesting that aging of the vasculature is a result of heritable epigenetic changes.